The senior target audience: when the body does not keep up with the youthful spirit, the clothing design gives a reply through comfort - Almeida, Mariana Dias de (2020)
The new image of older women has demystified the profile of fragile ladies and with simple aesthetics, this woman has some new or the same yearnings, and the unpreparedness of the clothing sector towards these women may lead us to believe that fashion does not know the true image of the new elderly woman, who can be simple as well as modern and articulate, which will depend on the repertoire that she has built. Thus with methodological guidelines that provide a clothing project with experience of the user’s reality, can provide greater inclusive direction of the elderly. Therefore, it is necessary to investigate the aspects of comfort in its in all dimensions, well-being, and valuation of clothing for elderly women from 65 to 85 years old. With the user-centred design methodologies and the aid of comfort assessment processes, we help to design apparel thought comfort for this increasingly demanding and purchasing power public target.